2017
DOI: 10.1002/ep.12541
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on combustion, performance, and emission characteristics of stationary CI engine fueled with diesel–methanol and biodiesel–methanol blends

Abstract: This article presents the experimental studies of the one‐cylinder, stationary diesel engine powered by blends of diesel and biodiesel with methanol. In the case of diesel–methanol mixture (DM) investigated, there is up to 40% of the alcohol content in the mixture, while in the case of biodiesel–methanol mixture (BM), the share of the alcohol was up to 50%. The normal combustion process achieved up to 30% of alcohol fraction. Further increase in the alcohol content led to a significant drop in cylinder pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The exergy analysis showed a 25.64% increase in exergetic efficiency [20]. Other researchers conducted similar studies [14,21,22]. They also confirmed that ethanol causes increase in engine efficiency.Co-combustion of ethanol with diesel fuel, as shown in the cited articles, has many advantages.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The exergy analysis showed a 25.64% increase in exergetic efficiency [20]. Other researchers conducted similar studies [14,21,22]. They also confirmed that ethanol causes increase in engine efficiency.Co-combustion of ethanol with diesel fuel, as shown in the cited articles, has many advantages.…”
supporting
confidence: 52%
“…On the one hand, ethanol reduces the temperature on the compressed load due to the high heat of vaporization. On the other hand, it increases the value of the maximum pressure and, consequently, the combustion temperature, contains additional oxygen in the structure, it promotes the formation of NO x [12][13][14]. Ethanol greatly affects the combustion stage.…”
mentioning
confidence: 99%
“…Also, the blends are not stable and separate in the presence of trace amounts of water. In such a power system can not change the ratio of diesel /alcohol [4][5][6][7][8][9][10]. The co-combustion of fuels blends is interesting as well.…”
Section: Introductionmentioning
confidence: 99%
“…The co-combustion of fuels blends is interesting as well. In papers [4][5][6][7][8][9][10] are presented results of the investigation of co-combustion of alcohol fuels with diesel or biodiesel fuels. It was stated that the combustion process in the dual fuel engine fueled with diesel and alcohol fuels has different pattern compared to combustion in the conventional compression ignition engine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation